4 - 9x = 29 - 4x

Question|Rated good

Asked 6/19/2011 10:01:42 PM

Updated 8/10/2014 5:38:45 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [8/10/2014 5:38:44 PM]

Expert answered|vchutkan|Points 1020|

Expert answered|vchutkan|Points 1030|

Expert answered|vchutkan|Points 1030|

Expert answered|vchutkan|Points 1030|

Expert answered|GaryR111|Points 0|

Question|Rated good

Asked 6/19/2011 10:01:42 PM

Updated 8/10/2014 5:38:45 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [8/10/2014 5:38:44 PM]

Rating

There are no new answers.

21 (x - 1) + x = 100 - 2 (x - 1)

Question

Not Answered

Updated 2/18/2014 3:26:07 PM

1 Answer/Comment

21 (x - 1) + x = 100 - 2 (x - 1)

21x - 21 + x = 100 - 2x + 2

22x -21 = 102 - 2x

22x + 2x = 102 + 21

24x = 123

x = 123/24

X = 41/8

21x - 21 + x = 100 - 2x + 2

22x -21 = 102 - 2x

22x + 2x = 102 + 21

24x = 123

x = 123/24

X = 41/8

Added 2/18/2014 3:26:07 PM

This answer has been confirmed as correct and helpful.

5x + 5 (x - 3) = 15
**Weegy:** x=3 (which would make it 15 + 0 = 15) **User:** x + 3 (x - 4) = 2 (x - 2) - 20
**Weegy:**
((3 / 5) * 0.6) - ((2 / 3) * 0.15) = 0.26 Thanks for asking Weegy. **User:** 10 - 5 (x - 5) = 4 (x - 1)
**User:** The sale price of a suit is three-fifths of the original price. Let p denote the original price of the suit. Express the sale price of the suit in terms of p **Weegy:** The answer is 25. (More)

Question

Expert Answered

Updated 8/10/2014 5:29:23 PM

3 Answers/Comments

5x + 5 (x - 3) = 15;

5x + 5x - 15 = 15;

10x = 15 + 15;

10x = 30;

x = 30/10;

x = 3

5x + 5x - 15 = 15;

10x = 15 + 15;

10x = 30;

x = 30/10;

x = 3

Added 8/10/2014 5:27:11 PM

This answer has been confirmed as correct and helpful.

x + 3 (x - 4) = 2 (x - 2) - 20;

x + 3x - 12 = 2x - 4 - 20;

4x - 12 = 2x - 24;

4x - 2x = -24 + 12;

2x = -12;

x = -12/2;

x = -6

x + 3x - 12 = 2x - 4 - 20;

4x - 12 = 2x - 24;

4x - 2x = -24 + 12;

2x = -12;

x = -12/2;

x = -6

Added 8/10/2014 5:28:06 PM

This answer has been confirmed as correct and helpful.

10 - 5 (x - 5) = 4 (x - 1);

10 - 5x + 25 = 4x - 4;

-5x + 35 = 4x - 4;

-5x - 4x = -4 - 35;

-9x = -39;

x = -39/-9;

x = 13/3

10 - 5x + 25 = 4x - 4;

-5x + 35 = 4x - 4;

-5x - 4x = -4 - 35;

-9x = -39;

x = -39/-9;

x = 13/3

Added 8/10/2014 5:29:23 PM

This answer has been confirmed as correct and helpful.

-4k2(7k2 - 2k + 1)
**Weegy:** 7 3/4 - 3/8 = 31/4 - 3/8; =62/8 - 3/8; = 59/8, as a mixed number 7 3/8 **User:** -4k2(7k2 - 2k + 1)
please multiply **Weegy:** 7 3/4 - 3/8 = 31/4 - 3/8; =62/8 - 3/8; = 59/8, as a mixed number 7 3/8 (More)

Question

Expert Answered

Updated 8/10/2014 5:39:41 PM

1 Answer/Comment

-4k^2(7k^2 - 2k + 1) = -28k^4 + 8k^3 - 4k^2

Added 8/10/2014 5:39:40 PM

This answer has been confirmed as correct and helpful.

27,681,710

questions answered

There are no comments.